The effects of climate change on a small open economy - George Economides; Anastasio Xepapadeas (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate the impact of climate change on the macroeconomic performance of a small open economy. The setup is a new Keynesian dynamic stochastic general equilibrium model of a small open economy without monetary policy independence in which a climate module that interacts with the economy has been incorporated. The model is solved numerically using common parameter values, fiscal data and projections about temperature growth from the Greek economy. Our results, suggest that climate change implies a significant output loss and a dramatic deterioration of competitiveness.
Keywords: E50; E10; Q50; 330; climate change; monetary policy; new Keynesian models